The First Decade: the 1970s. (June 2019) - Tearle, Barbara
Abstract: In this combined article, five authors provide a brief summary of the activities of the British and Irish Association of Law Librarians (BIALL) and the developments in law librarianship over the past 50 years, each writing about a different decade. Barbara Tearle (writing about the 1970s), Christine Miskin (the 1980s), Michael Maher (1990s), Fiona Fogden (2000s) and Narinder Toor (2010s) each bring their own experiences and memories to their writing and complete a half century of reflections to coincide with BIALL's 50 th anniversary in 2019.